2019
DOI: 10.1097/ede.0000000000000984
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Influenza-associated Morbidity and Mortality

Abstract: Background: Although smoking has been recognized as a risk factor for many respiratory diseases, its effects of influenza-associated morbidity and mortality remain controversial. We conducted a systematic review and meta-analysis to assess the impact of smoking on influenza-associated hospital admissions, intensive care unit (ICU) admissions, and deaths. Methods: We searched the databases of PubMed, CINAHL, EMBASE, and the China National Knowledge Infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
52
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 71 publications
6
52
3
4
Order By: Relevance
“…Smoking history was another pedictor of FluA-p mortality in our study, which is a finding commensurate with some previous reports [34][35][36]. Wong and colleagues, for example, found that influenza-related mortality for all-causes and for cardiovascular and respiratory diseases was greater in current and exsmokers than in never smokers [34].…”
Section: Discussionsupporting
confidence: 92%
“…Smoking history was another pedictor of FluA-p mortality in our study, which is a finding commensurate with some previous reports [34][35][36]. Wong and colleagues, for example, found that influenza-related mortality for all-causes and for cardiovascular and respiratory diseases was greater in current and exsmokers than in never smokers [34].…”
Section: Discussionsupporting
confidence: 92%
“…Smokers are 34% more likely than non-smokers to contract the flu [6]. Han and colleagues conclude that literature evidence showed that smoking was consistently associated with a higher risk of hospital admissions after influenza infection [7]. Smoking is the primary etiological factor behind chronic obstructive pulmonary disease (COPD) in the developed world, but environmental pollution and degrading air quality are also responsible in developing countries.…”
mentioning
confidence: 99%
“…Previous studies have shown that current smokers are more likely to have fewer health‐conscious behaviours including receiving an influenza vaccine 22 . Furthermore, a recent meta‐analysis has demonstrated that smoking is consistently associated with a higher risk of hospital admissions after influenza infection 3 . While we have only captured a small number of smokers in our program, smokers’ understanding of influenza severity could be a potential area of intervention to improve uptake of influenza vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Certain groups within the population are identified as being at higher risk of complications related to influenza infection. They include people aged >65 years; children aged <5 years; Aboriginal and Torres Strait Islander Peoples; people with Down syndrome; pregnant women; homeless people; smokers; and those with chronic diseases and other health conditions such as cardiac disease, obesity, chronic respiratory conditions, chronic neurological conditions, immunocompromised conditions, chronic liver disease and diabetes mellitus 2,3 . While there is no unified definition of ‘hard‐to‐reach’ populations, studies exploring influenza vaccine coverage for this group have generally included ethnic minorities, immigrants and homeless people 4–6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation